The Effect of Capital, Operating Hours, and Location Access in Increasing Merchants' Income at Legian Beach - Suriana, Ida; Bagiada, I Made (MEC-J (Management and Economics Journal), 2023)
The purpose of this study was to determine the effect of capital, operating hours and location access in increasing the income of traders at Legian Beach. This research uses quantitative methods. This study used 82 samples of merchants who sell on Legian Beach. The analysis technique used is path analysis using the PLS3 application.  The results showed that capital and location access had a significant positive effect on the income of traders on Legian Beach while one variable, namely operating hours, had no effect on the income of traders on Legian Beach.Keywords:  Capital, Operating Hours, Location Access and Income.